Studi Komparasi Fungi Mikoriza Arbuskula Asal Dua Ekosistem pada Perbaikan Pertumbuhan dan Hasil Kembang Kol di Media Gambut - Sasli, Iwan; Abdurrahman, Tatang (Universitas Bangka Belitung, 2024)
The success factor in developing arbuscular mycorrhizae fungal (AMF) biofertilizers the source of propagules, which is determined by ecological factors. The compatibility between AMFs is important in deciding whether the biofertilizer produced can be used efficiently. The research aims to study and obtain location-specific AMF from two different ecosystems on the growth and yield of cauliflower plants with efficient fertilization. The research was conducted in Pontianak City, West Kalimantan, from June to November 2023. The research method used a completely randomized factorial design. The first factor is the ecosystem source of AMF propagules (without AMF, AMF from peat ecosystems, and AMF from dry land ecosystems). The second factor is the level of NPK fertilization (100%, 75%, 50%, and 25% of the recommended dose). The research results obtained show that the application of AMF from peat ecosystems and dry land as a biological fertilizer is able to support the efficiency of NPK fertilization in increasing the growth and yield of cauliflower plants up to a fertilizer level of 50% of the recommended dose.